Clinical, biochemical, and genetic analysis of the mitochondrial respiratory chain complex I deficiency. Issue 32 (August 2018) - Ma, Yan-Yan; Li, Xi-Yuan; Li, Zhi-Qin; Song, Ji-Qing; Hou, Jing; Li, Jian-Hua; Sun, Li; Jiang, Jun; Yang, Yan-Ling
Abstract : Abstract: Mitochondrial respiratory chain complex I deficiency is one of common mitochondrial disorders. However, the information is relatively little about the features of Chinese patients. In this study, the clinical, biological, and genetic analyses were performed in the children with respiratory chain complex I deficiency, in order to further understand the characteristics of the disease. Over a 3-year period, 67 patients (37 boys, 30 girls), presenting with unexplained multisystemic symptoms and signs were recruited. Clinical and laboratory data of the patients were summarized. Spectrophotometric assay was used for the analysis of mitochondrial complex I-V enzyme activity in peripheral leukocytes. The entire mitochondrial DNA (mtDNA) sequence was analysed for patients and their mothers. The children with respiratory chain complex I deficiency presented with multisystem dysfunction. Onset occurred before the third year of life in 96.9% patients without mtDNA mutation. Onset occurred before the third year of life in 76.5% of patients with mtDNA mutation ( P  = .03). About 51.5% of patients without mtDNA mutation had weakness, which is higher than 24% patients with mtDNA mutation ( P  = .02). Isolated complex I deficiency and combined complex I deficiency were found in 45 and 22 patients, respectively. The prevalence of isolated complex I deficiency was higher in the patients with mtDNA mutations (79.4%) than in the patients without mtDNA mutations (54.5%). Patients with nuclear DNA mutations are more likely to develop early onset in mitochondrial respiratory chain complex I deficiency. The patients with complex I deficiency of peripheral leukocytes may be more likely to be caused by mtDNA mutation.